Steroid Treatment in Macular Edema: A Bibliometric Study and Visualization Analysis - Lin, Yu; Ren, Xiang; Chen, Danian (Frontiers in Pharmacology, 2022)
The use of steroids to treat macular edema (ME) is a hot topic in ophthalmology. We utilized CiteSpace and VOSviewer software to evaluate the publications received from the Web of Science Core Collection in a bibliometric method and build a visualizing map to describe the research progress in this topic. There were 3,252 publications in all. The number of studies in the ME literature about steroid therapy has risen year after year. These publications came from 83 countries/regions, with the United States, Germany, and Italy leading the pack. Most studies were published in Investigative Ophthalmology Visual Science, and Ophthalmology was the most cited journal. We found 9,993 authors, with Bandello F having the most publications and Jonas JB being the most frequently co-cited. The most popular keyword, according to our research, is triamcinolone acetonide. ME, diabetic macular edema, retinal vein occlusion, dexamethasone, fluocinolone acetonide, and some other keywords are also being studied in this area. Overall, we discovered steroid hotspots and developmental tendencies in ME. Many clinical studies for these medications and disorders are currently continuing, and improved clinical data and therapeutic options are anticipated to emerge in the future.